2021
DOI: 10.3390/molecules26102915
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile and Antioxidant Activities of Coleus amboinicus Lour. Cultivated in Indonesia and Poland

Abstract: Coleus amboinicus Lour., Lamiaceae, is a perennial herb that is native to Indonesia and also cultivated in Africa, Asia and Australia. The major phytochemicals responsible for its bioactivity are rosmarinic acid (RA) and its analogues, flavonoids and abietane diterpenoids. The possibility of cultivation in a colder climate would extend the use of this herb and provide new opportunities to herb growers and livestock farmers. Our study to compare feed value and phytochemical composition of C. amboinicus plants c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Polyphenol concentration in PLM was comparable to the finding of Huang et al, [9] study (26.94 mg/g DM and 24.6 mg/g DM, respectively) with Paulownia leaves. The differences in Paulownia leaves materials may be a cause of divergent agronomic management [12] than soil condition. Acteoside was the dominant bioactive substance amongst analyzed polyphenol compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphenol concentration in PLM was comparable to the finding of Huang et al, [9] study (26.94 mg/g DM and 24.6 mg/g DM, respectively) with Paulownia leaves. The differences in Paulownia leaves materials may be a cause of divergent agronomic management [12] than soil condition. Acteoside was the dominant bioactive substance amongst analyzed polyphenol compounds.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that they have the potential to modulate ruminal microbial fermentation mitigating methane production [10,11]. However, it should be kept in mind that the content of bioactive components may differ among the same species grown under different conditions [12]. Research conducted by Huang et al [9] showed that different levels of bioactive components in Paulownia leaves and Paulownia leaves silage, differing in polyphenolic content (25 vs. 47 mg/g dry matter (DM)), may have different effects on rumen fermentation, including methanogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The DPPH radical scavenging activity of the compound was determined according to the method of Ślusarczyk et al with slight modifications [ 11 ]. Briefly, 0.2 mM solution of DPPH in methanol was prepared and 2.5 mL of this solution were added to 2.5 mL of compound solution in methanol at different concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…All analyses were performed in triplicate. The present analysis procedure on phenolics fraction was following previous published study [14].…”
Section: Determination Of Phenolic Acid Avonoid and Diterpenoid Contentsmentioning
confidence: 99%
“…(CAL) herb is rich in polyphenolic compounds (mostly phenolic acids and avonoids), diterpenes, and alkaloids [10][11][12][13].C. amboinicus grows in tropical regions, including Asia, Africa and Australia, and is used in human medicine for long time [10,14]. Our previous short-term in vitro study revealed the capacity of CAL to decrease CH 4 production and to modulate ruminal FA composition, mainly n-3 polyunsaturated fatty acids (PUFAs) by altering the microbial activity linked to methanogenesis and FA biohydrogenation [13].…”
Section: Introductionmentioning
confidence: 99%